2017
DOI: 10.1007/s10853-017-0997-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boundary conditions on the evolution of lattice strains in a polycrystalline austenitic stainless steel

Abstract: The effect of boundary conditions (constant load, constant strain and elastic follow-up) on lattice strain evolution during creep in a polycrystalline austenitic stainless steel was studied using in situ neutron diffraction at 550°C. The lattice strains were found to remain constant under constant load control. However, under constant strain and elastic follow-up control, the lattice strains relaxed the most in the elastically softest lattice plane {200} and the least in the elastically stiffest lattice plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 18 publications
2
25
1
Order By: Relevance
“…2a and 2b, respectively. The uncertainties in the measured internal strains were approximately 30 microstrain[40].…”
mentioning
confidence: 93%
“…2a and 2b, respectively. The uncertainties in the measured internal strains were approximately 30 microstrain[40].…”
mentioning
confidence: 93%
“…al. [23] measured the evolution of lattice strains during creep dwells under different elastic-follow-up factors and found that under constant load control, the lattice strains in different grain families remained constant.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, as shown in Ref. 26, when the product of the relaxed lattice strain and the corresponding diffraction elastic constant were determined, it was found that stresses on the different crystal planes relaxed the same amount, and the trends in the relaxation of the lattice stresses agreed with the macroscopic stress relaxation. It should be noted that the DEC used in Ref.…”
Section: Resultsmentioning
confidence: 63%
“…It should be noted that the DEC used in Ref. 26 were obtained from the unloading stage rather than the loading up stages presented in the current work. More scientific discussion about the results can be found in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation